ETHNOMATHEMATICAL INSIGHTS FROM THE CULTURAL HERITAGE OF THE GREAT MOSQUE OF MADIUN - Krisdiana, Ika; Astuti, Indra Puji; Murtafiah, Wasilatul; Fisabilillah, Ainun (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
Ethnomathematics integrates mathematical concepts such as counting, measuring, geometric patterns, and spatial structures with local culture to create more meaningful and contextual learning. This study aims to explore the concept of ethnomathematics in the architecture of the Baitul Hakim Grand Mosque in Madiun City and assess its potential as a learning resource in mathematics learning. Using a qualitative ethnographic approach, data were collected through direct observation of the mosque building, interviews with mosque administrators, and architectural documentation. Data analysis was carried out systematically through method triangulation to ensure the validity of the findings. The results of the study revealed real mathematical activities in the mosque building, namely counting activities (the number of 120 pillars, 5 ablution places, and 1 tower), measuring (the height of the main pillar is 12m, the diameter of the pillar is 50cm, the ablution places are 3x3m and 5x12m, and the tower is 35m high with various diameters), and designing the building (combining elements of Javanese, Arabic, and European architecture). Further exploration shows the existence of flat geometry concepts (rectangle, isosceles triangle, trapezoid), solid shapes (cylinder, cuboid, cone, pyramid), and geometric transformation (reflection on the axis). The conclusion of this study shows that the structure of the mosque can function as a medium for learning mathematics based on culture that can increase learning interest and facilitate student understanding